Financial Statement Analysis to Assess Financial Performance at The Employees' Cooperative Center of Koperasi Pegawai Republik Indonesia Gajayana, Malang City - Maria Orlina Ndai; Cakti Indra Gunawan; Noviana Yaniar Suprajitno (International Research & Development for Human Beings (IRDH), 2026)
The purpose of this research is to provide an assessment of the financial performance of the Republic of Koperasi Pegawai Republik Indonesia Gajayana, Malang City during the 2020-2024 period. This type of research is qualitative descriptive. The data used are financial reports for the 2020-2024 period. Data analysis uses liquidity, solvency, activity, and profitability ratio analysis. The results of the study show that the financial performance of KPRI Gajayana Malang City, Indonesia, in 2020–2024 based on financial ratio analysis shows varying conditions. The liquidity ratio indicates a liquid condition because the Current Ratio, Quick Ratio, and Cash Ratio are above the industry standard so it can be said to be liquid. In the solvency ratio, the Debt to Asset Ratio has not met the industry standard so it can be said to be ineffective, while the Debt to Equity Ratio is still in the effective category. The activity ratio shows an ineffective condition because the turnover of inventory, receivables, and total assets are below the industry standard. In the profitability ratio, Net Profit Margin is mostly above the industry standard, but Return on Equity and Return on Investment are still low. Overall, the cooperative's financial performance shows a liquid condition and is able to generate profits, but the utilization of assets and capital is not optimal. Cooperative management needs to increase the effectiveness of accounts receivable management and optimize asset utilization so that the rate of fund turnover becomes faster and more productive.